2020
DOI: 10.14309/ajg.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Chronic Pancreatitis During Pregnancy and its Effect on Maternal and Fetal Outcomes

Abstract: Introduction: There are limited data on the effect of chronic pancreatitis (CP) on pregnancy outcomes and vice versa. Our aim was to evaluate the clinical trajectory of CP during pregnancy and its effect on pregnancy outcomes. Methods: All female patients of child-bearing age (≥15 years) diagnosed with CP were studied from January 2004 to July 2019. The change in frequency of painful episodes was assessed before, during, and after pregnancy. Maternal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This shows that the maternal and fetal outcomes were comparable in all three groups. One of the authors has published an article on maternal and fetal outcomes in pancreatitis and reported no increased risk of maternal and fetal outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the maternal and fetal outcomes were comparable in all three groups. One of the authors has published an article on maternal and fetal outcomes in pancreatitis and reported no increased risk of maternal and fetal outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is so important to care for a pregnant woman in such a way that (thanks to early diagnosis), it is possible to prevent the development of acute pancreatitis, and if the disease develops, it could be properly treated. Children born to mothers diagnosed with hypertriglyceridemia during pregnancy have impaired lipid homeostasis and are more prone to atherosclerosis [ 38 ].…”
Section: Comprehensive Management Of Ap In Pregnant Womenmentioning
confidence: 99%
“…This is still the case outside reference centers. Hence, the main cause of CP in pregnant women is alcohol abuse, and the second is idiopathic CP, but it should be assumed that, in both of these groups, mutations predisposing to CP can be found in the majority of women [ 38 ].…”
Section: Comprehensive Management Of Ap In Pregnant Womenmentioning
confidence: 99%
“…8 Another study of 57 patients with CP reported no increased risk of adverse maternal and fetal outcomes and had benign clinical course of CP during pregnancy. 9 The motherhood is a most important and desirable lifetime event for females. However, in cases of patients suffering from chronic gastrointestinal disorders, the course of pregnancy and postnatal period may get complicated resulting in adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…Eddy et al reported 11 patients of CP in a cohort of 101 patients with pancreatitis with limited information on clinical outcomes in patients with CP 8. Another study of 57 patients with CP reported no increased risk of adverse maternal and fetal outcomes and had benign clinical course of CP during pregnancy 9…”
mentioning
confidence: 99%